Strengthening household resilience for enhanced food security in northwestern Ethiopia: insights from resilience pillars - Abebe, Mekonen Getachew (Frontiers in Sustainable Food Systems, 2025)
IntroductionEthiopia has faced significant food insecurity challenges, impacting households from the district to the national level. To strengthen household resilience to food security, it is essential to assess their current resilience levels accurately. The main objective of the study was to assess rural household resilience to food insecurity in Libo Kemkem, a district in northwest Ethiopia, which is particularly susceptible to food insecurity, and identify the contributions of the key pillars that enhance households' capacity to cope with food insecurity.MethodologyThe research used a cross-sectional survey with 216 households, drawn using a multi-stage stratified sampling technique to ensure representation across different subgroups. The Food and Agricultural Organization's Resilience Index Measurement and Analysis II framework was applied to assess the levels of resilience. Factor analysis was used as the main analytical tool to estimate the household resilience index.Result and discussionThe result indicated that asset, adaptive capacity, and access to basic services are highly contributed to resilience with positive scores of scores of 0.85, 0.82, and 0.81 respectively. All the aforementioned scores of resilience pillars are highly significant since it is greater than 0.37 which is recommended for a sample size of 200 and above. Nevertheless, the social safety net is negatively associated with resilience, with a score of 0.68. The average household resilience capacity index was 0.56, showing that 63% of households are less resilient. The overall results of the study showed that households with better assets, adaptive capacity, and better access to basic services, are likely to be more resilient. Consequently, this study recommends applying targeted resilience-oriented strategies programs, packages, and projects that improve these positively contributing pillars of resilience to enhance food security in the area.